Review of Islamic Law on the Practice of "Paylater" in Buying and Selling Transactions - Shevira Arista Achmanda (Alhurriyah, 2023)
PayLater is a financial facility in the form of a payment method with installments without a credit card. E-commerce transactions are legal as long as the goods sold are in accordance with the details, pictures, and illustrations displayed on the internet page. This research is included in the category of literature study, and if viewed from the side of the research paradigm, it is a type of descriptive-qualitative research. After an in-depth study, it was concluded that if the practise of PayLater in buying and selling transactions is allowed for clear contractual reasons and judging from the general argument that allows it and also the nash that prohibits it, it does not exist. The important thing is that the price increase on the suspension is still at a fair and reasonable price, and there is no element of coercion between the two parties. However, it needs to be balanced based on an understanding of the potential risks it poses, such as consumptive and the risk of debt, if not used wisely and carefully.PayLater adalah sebuah fasilitas keuangan yang berupa metode pembayaran dengan cicilan tanpa adanya kartu kredit. Transaksi e-commerce sah hukumnya selama barang yang dijual belikan sesuai dengan rincian, gambar dan ilustrasi yang dipajang di laman internet. Penelitian ini termasuk kategori studi literature yang ditinjau dari sisi paradigma penelitian maka termasuk jenis penelitian deskriptif-kualitatif. Setelah dilakukan kajian mendalam diperoleh sebuah kesimpulan bahwa praktik PayLater dalam transaksi jual beli diperbolehkan dengan alasan akad yang jelas dan karena dilihat dari dalil umum yang membolehkan dan juga nash yang mengharamkannya tidak ada, yang penting penambahan harga pada penangguhannya masih dengan harga yang pantas dan sewajarnya, dan tidak ada unsur pemaksaan antara kedua belah pihak. Namun perlu diimbangi berdasarkan pemahaman atas potensi risiko yang ditimbulkannya, seperti konsumtif dan resiko berhutang jika tidak dipergunakan secara bijaksana dan seksama